SCIENTIFIC AND METHODICAL BASES OF PERFECTION ENTERPRISE CAPACITY ASSESSMENT - Gonchar, Olga (Науковий вісник Полісся, 2017)
Urgency of the research. The importance of clarifying approaches to potential assessing has occurred due to the need to substantiate decisions on potential management. Target setting. It is expedient to assess the state and development level of enterprise industrial potential, taking into account the key factors to ensure effectiveness and efficiency of activity. Actual scientific researches and issues analysis. The following scholars made studies on various aspects of enterprise assessment capacity: O. B. Alokhin, A. B. Brutman, A. E. Voronkova, I. M. Karapeichyk, M. V. Sharko, A. V. Cherep. Uninvestigated parts of general matters defining. The original concept of capacity assessment is ambiguous and it is wrong to associate it only with the categories of income, profit, costs, and coefficients expressing a measure of financial performance, which takes place in the main part of the current studies. The research objective. The objective in the article is to clarify and supplement the existing scientific approaches to enterprise economic potential assessment, to substantiate the author’s specification of methods and indicators for its implementation. The statement of basic materials. The results of studying aspects of enterprise economic potential assessment are summarized. The process of capacity assessment is defined as a solid analytical and information process of calculating the quantitative or qualitative characteristics of potential value. For this indicators adopted in economics to describe the results of the statutory activities are used. Based on the author’s definition of enterprise potential, as the ability to realize the possibility it is stated that its immediate assessment is impossible and can only be indirectly conducted via achievements and effectiveness. Attention is drawn to the fact that capacity assessment model should include the integration of internal and external manifestations of it, the sequence of actions; It must be capable of determining the state of the problematic aspects and opportunities for further development. It is proved that while potential assessing manager has to examine the composition and level of development of its components, as well as the impact of individual factors. The evaluation process should be carried out in such a way as to consider and identify the characteristics of all business processes, monitoring and evaluation. Conclusions. Assessment capacity theory is at a formative stage and needs to be clarified. The proposed method of monitoring information support and complement the assessment methods will contribute to the improvement of management capacity